Oscillatory Stability Prediction using PSO Based Synchronizing and Damping Torque Coefficients - A. M. Kamari, N.; Musirin, I.; A. Hamid, Z.; H. M. Zaman, M. (Bulletin of Electrical Engineering and Informatics, 2018)
This paper presents the assessment of stability domains for the angle stability condition of the power system using particle swarm optimization (PSO) technique. An efficient optimization method using PSO for synchronizing torque coefficients Ks and damping torque coefficients Kd to identify the angle stability condition on multi-machine system. In order to accelerate the determination of angle stability, particle swarm optimization (PSO) is proposed to be implemented in this study. The application of the proposed algorithm has been justified as the most accurate with lower computation time as compared to other optimization techniques such as evolutionary programming (EP) and artificial immune system (AIS). Validation with respect to eigenvalues determination, Least Square (LS) method and minimum damping ratio Î¾min confirmed that the proposed technique is feasible to solve the angle stability problems.